Avaliação, identificação e encaminhamentos de estudantes com deficiência intelectual na rede municipal de ensino de Manaus - Queiróz, Julia Graziela Bernardino de Araujo (2023)
The present study had the general objective of analyzing the evaluation and referral process of students with intellectual disabilities at Semed (Rede Municipal de Ensino de Manaus), based on the action of the Municipal Complexo Municipal de Educação Especial (CMEE). The specific objectives were based on: analyzing the normative documents arising from Semed's public policies for school inclusion in terms of the evaluation process of special education students; discuss Semed data regarding the enrollment flow of students with intellectual disabilities in the period from 2016 to 2022; characterize the evaluation process of students with intellectual disabilities in the CMEE and discuss the referrals made by the CMEE for students with intellectual disabilities and their effects on the schooling path. The theoretical assumption was based on systemic thinking, with the contributions of Maturana and Varela (2001), Vasconcellos (2002) and Pellanda (2009). As for the methodological aspects, it was based on the qualitative approach and an Integrative Review was carried out, aiming to produce an interlocution with the specific literature linked to the theme. Semed was constituted as the locus of the investigation, through the CMEE, in which an analysis of the normative documents of the municipality on the evaluation of the target public of Special Education was produced and semi-structured interviews were carried out with 7 professionals who work in the CMEE. The analysis of documents and interviews was produced using the ATLAS.ti software, which enabled the construction of analytical axes. The research results showed that the process of identifying students referred to the CMEE starts with the school or professional in the clinical area. The students assisted with a medical report are, for the most part, in a situation of social vulnerability, aged between 6 and 10 years, a period in which difficulties in the literacy process are observed. It was verified that Semed presents a series of documents and actions that contemplate Special Education, however, there is a lack of definition of the adopted policy. Given this context, one can observe Semed's challenge with regard to actions for these students, considering the clinical perspective that supports the understanding of intellectual disability, the process of evaluation and referral to different areas of special education and support services, implying in the pedagogical issues and in the schooling of these students.